Extraarticular Posttraumatic Ankylosis (Case Report) - V. Zbořil; J. Pazdera; J. Novotný (Czech Dental Chamber, 2006)
The authors demonstrate the case of extraarticular ankylosis, originated on the basis of superfluous formation of osseous tissue (callus luxurians) as a consequence of traumatic affection of the area of the ramus of mandible and possible diagnostic and therapeutic obstacles, connected with this disease.